AN EMPIRICAL INVESTIGATION OF THE EFFECTS OF CAPITAL STRUCTURE, LIQUIDITY, GROWTH OPPORTUNITY, AND COMPANY SIZE ON THE PROFITABILITY OF FINANCIAL SECTOR SERVICE COMPANIES AT FINANCING INSTITUTIONS LISTED ON THE INDONESIA STOCK EXCHANGE - Anita Widyawati; Etty Soesilowati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The study was carried out with the aim of examining the effect of capital structure, liquidity, growth opportunity, and company size on the profitability of financial institutions listed on the Indonesia Stock Exchange from 2016 to 2020. This study's sample consisted of ten companies chosen using the target sampling method. Using the E-Views 10 software, multiple linear regression analysis was used to analyze the relationship between the independent factors and the dependent variable. The findings revealed that capital structure and liquidity had no effect on profitability, whereas growth opportunity and company size had a significant effect. The research's limitations include the limited number of data units and the inclusion with only financial sector enterprises in the financial institutions sub-sector. This study reflects investors and business management in making financial decisions based on the variables examined.